The influence of placenta microbiota of normal term pregnant women on immune regulation during pregnancy - Ping Yang; Tong Lu; Xinyuan Liang; Ting Huang; Lulu Wu; Zonglin He; Xiaomin Xiao; Shangrong Fan (BMC, 2024)
Abstract Background The concerted regulation of placenta microbiota and the immune responses secures the occurrence and development of pregnancy, while few studies reported this correlation. This study aimed to explore the relationship between the placenta microbiota and immune regulation during pregnancy. Methods Twenty-six healthy pregnant women scheduled for elective cesarean section in the First Affiliated Hospital of Jinan University who met the inclusion criteria were recruited. Placenta and peripheral venous blood samples were collected. Microbiota in placental tissue was detected using high-throughput sequencing. Flow cytometry was used to detect immune cells in placental tissue and peripheral venous blood. ELISA and Luminex liquid chip technology were used to detect the content of cytokines in placental tissue and peripheral venous blood, respectively. Results The placental microbiota has stimulating effects on the local immunity of the placenta and mainly stimulates the placental balance ratio CD56 + CD16 + /CD56 + CD16 and the placental macrophages, that is, it plays the role of immune protection and supporting nutrition. The stimulating effect of placental microbiota on maternal systemic immunity mainly induces peripheral Treg cells and B lymphocytes. Conclusion The placental microbiota may be an important factor mediating local immune regulation in the placenta, and placental microbiota participates in the regulatory function of the maternal immune system.